Knowledge and Acceptance of Labour Analgesia in Pregnant Women - Sharma, Mona; Dhungel, Saurya; Niroula, Sujata; Karki, Manan (Journal of Nepal Health Research Council, 2018)
Background: Labour analgesia, though practiced worldwide, is not very popular in low-income countries. The aim of the study was to assess the awareness, attitude, acceptance, and reasons for hindrance of labour analgesia among patients visiting a tertiary care center in the capital city Methods: It was a cross sectional study conducted in Obstetrics and Gynecology outpatient department of Kathmandu Medical College Teaching Hospital in the month of August 2017. All pregnant patients presenting for antenatal checkup was included. Data was collected based on a questionnaire after informed consent. Statistical analysis was done in SPSS version 20 and results were expressed in frequencies and percentage. Results: Total of 270 pregnant women participated in the study. Out of these forty-four (16.3%) patients were aware about labour analgesia. The acceptance rate was high (72.2%). Majority (84.6%) had no problem with expenditure associated with labour analgesia. Conclusions: Despite low awareness about painless delivery among the antenatal women, the acceptance rate is high.